COLETA SELETIVA E RECICLAGEM COMO INSTRUMENTOS PARA CONSERVAÇÃO AMBIENTAL: UM ESTUDO DE CASO EM UBERLÂNDIA, MG / Separate collection and recycling as instruments to environmental conservation: a case study in Uberlândia, MG, Brazil - Oswaldo Marçal Júnior; Erika Yano Hisatugo (Sociedade & Natureza)
One of the biggest problems of urban centers is the final disposal of waste, the capitalist systemmakes this situation worse. The separate collection and material recycling are among theprincipal solutions to this problem. This study aims to determine the quantity of collectedmaterials from a separate collection company from the city of Uberlândia (MG) and to evaluatethe environmental gains from this process. In the period 2001/2004, the activities carried outby the company were accompanied by the researcher, who also had access to the data registersregarding to the separation, classification and weight of recyclable materials. This data wereused to calculate the potential savings in terms of energy and natural resources. In total, therewere 4.727,74 t. of recyclable materials collected. The mean weight of aluminum deviated from the landfill was 8,22 t/year, this may provide a bauxite saving of 41,1 t. The mean weight ofpaper was 804,26 t/year, allowing a water saving of 19.571,63 thousand of liters. The meanweight of plastic was 369,51 t/year. We remind that plastics recycling provides saving of animportant non-renewable resource: oil. The results indicate that the separate collection andmaterials recycling may offer significant economics and environmental gains to the city ofUberlândia.